The Function of Natural Polysaccharides in the Treatment of Ulcerative Colitis - Guo, Yafei; Li, Yang; Cao, Qiang; Ye, Leilei; Wang, Junmei; Guo, Mei (Frontiers in Pharmacology, 2022)
Ulcerative colitis (UC) is an inflammatory bowel disease that is persistent and nonspecific. There are several medications available for the treatment of UC. However, conventional UC medications have substantial adverse effects, low clinical effectiveness, and a high recurrence rate. Therefore, it is critical to discover new medicines that are both safe and effective for UC patients. Natural polysaccharides offer a wide range of pharmacological benefits, including anti-inflammatory, anti-virus, anti-tumor, anti-aging, immune enhancement, and gut flora regulation. In the therapy of UC, natural polysaccharides can modulate inflammatory factors, the immune system, and intestinal flora, and preserve the intestinal mucosa. It demonstrates a good curative effect and is of safety to use, thereby being a potential treatment for UC patients. This paper covers the structure, the pharmacological effects on UC, and the mechanisms of natural polysaccharides. Finally, limitations, challenges, and perspectives are discussed. It is hoped that the findings of this publication will inspire more natural polysaccharides research and provide a theoretical foundation for the creation of new UC medications.